The contribution of psychogenic factors limiting prolonged work performed at different relative intensities - Rorke, Stafford Conroy (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1986)
This study investigated the physiological and psychological limitations to prolonged work performed at different relative intensities, through the use of an eclectic integrative methodology. Ten young male caucasian subjects (mean V0â‚‚ max. 60,0 ml.kgâ »Â¹.minâ »Â¹ Â± 7,9) were randomly exposed to treadmill runs at each of four relative intensities, namely 55%, 65%, 75% and 85% of V0â‚‚ maximum, with the instruction to run to the point of subjective discomfort at which they were no longer willing to continue. Physiological measures of oxygen consumption (V0â‚‚), heart rate (HR), respiratory exchange ratio (R) , minute ventilation volume (Vi), breathing frequency (Vf), tidal volume (Vt) and psychological measures of Ratings of Perceived Exertion (RPE), Perceived Thermal ComfoÂ·rt (PTC), Perceived Pain and Perceived Fatigue were recorded throughout the protocol. The relative intensity was held constant by slight decreases in treadmill speed as subjects fatigued, and through feedback from an on-line oxygen consumption computer-aided data acquisition system. Significant increases in both physiological and psychological measures occurred with increases in relative intensity (p<0,05). HR and Vf increased overtime (p<0,05) whilst Rand Vt decreased over time (p < 0,05) . All psychological ratings increased in intensity over time (p < 0,05). Mean endurance times to exhaustion were 243 minutes Â± 70 at 55% relative intensity, 159 minutes Â±37 at 65%, 96 minutes Â±25 at 75 % and 23 minutes +- 8 at 85%, being within the range reported by earlier researchers . A regression equation for prediction of endurance time given a known relative intensity was developed for this sample: % V0â‚‚ max. = 117,8 + (-10,6 x LN (time)) (where r = -0,91) Convergence rankings indicate the greater contribution of local factors in the overall gestalt of perceived exertion, pain and fatigue, with biomechanical limitations to prolonged work (running) strongly implicated . High inter correlations between psychological rating scales suggest the use of the scale considered most applicable to the task at hand and the psychological response measure required. A coefficient of multiple correlation of 0,94 established the close interrelationship amongst the physiological and psychological parameters measured. Pre- and post-test Fatigue Cluster Analysis questionnaires indicated that the most important clusters contributing toward the sensation of fatigue and subsequent decision to cease activity were Task Aversion and General Fatigue (r = 0,96), followed by Leg Fatigue and Thirst. Motivation, the task at hand and an attainable goal appear to be important considerations in prolonged work performance. Relative intensity appears a valid tool for use in prolonged work studies due to its high predictive capacity for endurance performance times (r=-0,91). It is concluded that workloads considerably below 55% of maximal aerobic capacity are indicated as acceptable workloads for an 8 hour working day.
Keywords: Physical fitness -- Measurement; Physical fitness -- Psychological aspects; Work measurement; Work -- Psychological aspects